GENETIC POLYMORPHISM OF ASTHMA IN IRAQ - Atta, R. Z.; Aloubaidy , R. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This case-control study was conducted to evaluate the influence of interleukin (IL) - 17A and -17F gene polymorphisms on the risk of asthma. In the present study blood samples were collected from 45 asthma patients and 50 healthy controls. Serum levels of cytokines interleukin-17A and interlukin-17F (IL-17A and IL17F, respectively) and immunoglobulin E (IgE) were measured using ELISA kit in both subjects. Serum levels of IL-17A and IgE were shown a higher significant differences (p< 0.05) while no significance difference ( p>0.05 )of IL-17F was shown in serum levels in comparison with controls .  The frequency of the allele and genotypes in the patient groups and control groups were determined using Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP). IL-17A gene amplified using specific primers then digested by (XagI) restriction enzyme, in order to detect (G197A) (rs2275913) SNP. While IL-17F gene amplified using specific primers then digested with (Nla III) restriction enzyme to detect (A7488G) (rs763780) SNP. There were no significant differences between asthma patients and wild type GG and G allele and mutant type AA and A allele for IL-17A SNP (GG: OR 1.71, P=0.284, G: OR 1.71,  P=1.00, AA: OR 1.99,  P =0.294, A: OR 0.96, P=1.00) while the mutant type AG for  mentioned SNP was determined and tested for their association significantly with asthmatic patients (OR 0.39, P=0.039). Frequencies of IL-17F genotype AA and allele A and mutant type AG or GG were found no associated with asthma patients.